Mediação e autonomia privada - Rossi, Alina de Toledo (2019)
The current study aims to analyze how mediation relates to private autonomy, including changes resulting from mediation law and Brazilian Code of Civil Procedure, and to show how the institute is currently regulated by national legislation. The current legislative changes on mediation and conciliation demand attention and study by legal operators. Likewise, a new conception of acess to justice lead us the need for discussion about methods for conflict resolution, these facts are the main justifications for this research. This study is carried out to show, first of all, a brief vision regarding the conflict, in order to next address general aspects of the mediation and conciliation, mentioning similarities and differences according to the law. The private autonomy principle is first dealt on a separated topic, the unavailability of rights is dealt with sequentially, so that it is possible to delimit the object of mediation and, consequently, private autonomy limits. Finally, the relationship between autonomy private principle and mediation is examined exclusively in order to verify its importance as a pillar of the institute, its relationship with the various fields of mediation, and also the question of the compulsory mediation provided for in the Brazilian Code of Civil Procedure. In the course of the study, it was found that the relationship between private autonomy and the need for State intervention for the protection of sensitive situations it is a very delicated balance